The Relationship Between Exchange Rates and Sustainable Development: A Literatur Review - Ismail, Syadan Hussein; Yuliadi, Imamudin; Berliana, Amanda (Universitas Muhammadiyah Yogyakarta, 2025)
The relationship between exchange rates and sustainable development has increasingly gained attention in global economic studies. Exchange rate fluctuations significantly impact foreign direct investment (FDI) and international trade, key drivers of sustainable development. Exchange rate stability contributes to the adoption of renewable energy in developing countries. This article presents a literature review using bibliometric analysis based on data from 59 academic articles from Scopus. The study identifies five key clusters that depict the interaction between exchange rates, FDI, carbon emissions, energy consumption, food security, and climate change. The analysis reveals that exchange rate stability is crucial in promoting sustainable development by encouraging green investments and reducing carbon emissions. These findings emphasize the importance of economic policies that support exchange rate stability to achieve sustainable development goals (SDGs). The novelty of this research is that it explains the relationship between monetary economic phenomena and environmental issues. This article offers new insights and recommendations for future research in this field.